We Walk: a person-centred, dyadic behaviour change intervention to promote physical activity through outdoor walking after stroke—an intervention development study - Stephan U Dombrowski; Brendan McCormack; Maggie Lawrence; Frederike Van Wijck; Jacqui H Morris; Linda A Irvine (BMJ Open)
Objectives To develop We Walk, a theoretically informed, 12-week person-centred dyadic behaviour change intervention to increase physical activity (PA) in community-dwelling people with stroke (PWS) through outdoor walking.Design Three-phase intervention development study. Phase 1: we reviewed literature on barriers and facilitators to PA after stroke and mapped them to the Behaviour Change Wheel and Theoretical Domains Framework to define intervention components. The Health Action Process Approach determined intervention structure underpinned by person-centred principles. Phase 2: stakeholder focus groups involving PWS, their companions and health professionals reviewed the draft intervention, and experts in behaviour change were consulted. Phase 3: informed by phases 1 and 2, the intervention and form of delivery were refined, with final review through patient and public involvement.Setting Three Scottish community rehabilitation stroke services.Participants Twenty-three ambulatory community-dwelling PWS and their companions, thirty-seven health and exercise professionals, seven behaviour change experts.Results Phase 1 determined key intervention components: information about benefits of walking; developing motivation and confidence to walk; facilitating dyadic goal setting and making plans together; monitoring walking, overcoming challenges; and maintaining walking behaviour. Phase 2 review by stakeholder focus groups and behaviour change experts endorsed intervention components and structure, emphasising dyadic relational aspects as central to potential success. In phase 3, intervention content and handbooks for PWS and buddies were finalised. Healthcare professionals proposed third-sector delivery as most appropriate for intervention delivery. A detailed delivery manual was developed. Participants preferred facilitated face-to-face and telephone delivery.Conclusions Our multilens intervention development approach ensured this novel intervention was evidence-informed, person-centred, theoretically coherent provided appropriate social support, and addressed issues of concern to PWS. This study established intervention components and structure and identified operational issues critical to future success. Future research will pilot and refine We Walk and evaluate acceptability, feasibility, effectiveness and cost-effectiveness.Trial registration number ISRCTN34488928.